Comparison of Mobile Software Therapy Versus Patching Therapy in Patients of Amblyopia - Boota, Wajeeha; Awan, Muhammad Anwar; Akram, Sayed Nishat; Jamil, Sana; Baig, Nosheen Aman (Medical Journal of South Punjab, 2025)
Objective: To compare visual acuity and stereoacuity improvement in anisometropic amblyopic patients undergoing software versus patching therapy.Methodology: It was a Quasi-experimental study conducted from December 2023 to May 2024 in Al Habib eye trust hospital, Shahdara and Eye department of Sardar Bibi Hospital, Ferozwala. The study involved 44 children aged 6-12 years with unilateral mild to moderate anisometropic amblyopia (?0.2 logMAR BCVA difference). Participants already undergoing two months of patching therapy were in the Patching Group; other preferring software therapy formed the Software Therapy Group. Visual and stereoacuity were assessed at baseline, 1st, 3rd, and 6th months.Results: At the 6-month, both software therapy (0.27 ± 0.19, p < 0.001) and patching therapy (0.27 ± 0.11 p = 0.003) significantly improved visual acuity. The Software Therapy Group achieved higher mean VA (0.32 ± 0.16) than the Patching Therapy Group (0.29 ± 0.11), with a significant difference (p = 0.022). Stereoacuity also significantly improved in both groups: Software Therapy (0.50 ± 0.29, p < 0.001) and Patching Therapy (0.43 ± 0.17, p = 0.002). Compliance favored software therapy (p < 0.001), indicating potential benefits over patching therapy for anisometropic amblyopia.Conclusion: Binocular software therapy excelled in improving visual and stereoacuity for mild to moderate anisometropic amblyopia, especially in younger children aged 6-9 years.